Serum 25-hydroxyvitamin D levels and psychological distress symptoms in patients with affective disorders during the COVID-19 pandemic - Di Nicola, Marco; Dattoli, Luigi; Moccia, Lorenzo; Pepe, Maria; Janiri, Delfina; Fiorillo, Andrea; Janiri, Luigi; Sani, Gabriele (Psychoneuroendocrinology, 2020)
•Psychiatric patients are more vulnerable to psychological impact of COVID-19 outbreak.•Hypovitaminosis D is frequent among patients with affective disorders.•A substantial rate of subjects with mood disorders displayed psychological distress during the pandemic.•Low 25(OH)D levels and Major Depression diagnosis predicted psychological distress severity.•Vitamin D might mediate the response to psychological stress in patients with affective disorders. Background. The COVID-19 pandemic has given rise to stress worldwide, especially in vulnerable people like those suffering from mental illness. This study aims to investigate the psychological distress perceived by a cohort of patients with Major Depressive Disorder (MDD) or Bipolar Disorder (BD) after a seven-week period of lockdown measures, and to analyze serum 25-hydroxyvitamin D [25(OH)D] levels as a potential predictor of distress severity. Methods. Fifty-nine remitted MDD and fifty-three euthymic BD patients were enrolled. An online dedicated survey was administered to obtain lockdown-related information and to evaluate COVID-19 related distress by using the Kessler 10 Psychological Distress Scale (K10). Patients’ medical records were reviewed to collect sociodemographic and clinical data, including serum 25(OH)D levels dosed in the three months preceding the outbreak. A multivariate general linear model was adopted to test the effect of factors of interest on psychological distress. Results. In our sample (n = 112), 29 subjects (25.9 %) reported no likelihood of psychological distress, whereas 35 (31.2 %) and 48 (42.9 %) displayed mild and moderate-to-severe likelihood of psychological distress, respectively. Low serum 25(OH)D levels (p = 0.005) and MDD diagnosis (p = 0.001) specifically predicted the severity of psychological distress. Living alone during the lockdown, a longer duration of illness, and smoking habits were more frequently detected in subjects with COVID-19 related distress. Conclusions. Low serum 25(OH)D levels and MDD diagnosis predicted an increased vulnerability to the stressful impact of the COVID-19 outbreak. Our results suggest that vitamin D may represent a biological factor mediating the psychological response to stress in individuals with affective disorders and provide further insight into tailoring intervention strategies.